Estimation of fretting fatigue life using a multiaxial stress-based critical distance methodology - F. C. Castro; J. A. Araújo; M. S. T. Pires; L. Susmel (Fracture and Structural Integrity)
This work presents a methodology for life estimation of mechanical couplings subjected to fretting fatigue. In this approach, a stress-based multiaxial fatigue parameter is evaluated at a critical distance below the contact surface. The fatigue parameter is based on an improved formulation of the Modified Wöhler Curve Method, in which the shear stress amplitude is measured via the Maximum Rectangular Hull method. To apply the Theory of Critical Distances in the medium-cycle fatigue regime, the critical distance is assumed to depend on the number of cycles to failure. Available fretting fatigue data, conducted on a cylinder-plane contact configuration made of Al alloy 4% Cu, were used to assess the methodology. Most of the life estimates were within an error band given by a factor of 2.